2015
DOI: 10.1136/heartjnl-2015-308066.166
|View full text |Cite
|
Sign up to set email alerts
|

166 T-tubule remodelling and formation of super-tubules in the border zone of cardiac myocytes in the infarcted pig heart

Abstract: BackgroundMyocardial infarction (MI) is a common cause of death, with approximately 175000 inpatient episodes of acute myocardial infarction in the UK in 2012. Following an MI the loss of cardiac myocytes triggers a remodelling process depositing extracellular matrix in the infarct region. Hypocontractile, damaged cardiac myocytes surround the infarct, forming a border zone. One of the key structural components regulating excitation-contraction coupling in the heart is the t-tubule network. Conventional confoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Alternatively, it could indicate different aetiologies which have not been understood yet. Pinali et al (2015) have observed ‘super-tubules’ in confocal micrographs and EM tomograms of ischemic border zone tissues following myocardial infarction. In dSTORM tissue imaging, we have observed analogous macro-tubules in a small subset of ventricular myocytes in aged (70–110 week old) mice which display normal cardiac function (Figures 3E,F ).…”
Section: Utility Of Nanoscale Resolution For Studying Couplon Remodelmentioning
confidence: 98%
“…Alternatively, it could indicate different aetiologies which have not been understood yet. Pinali et al (2015) have observed ‘super-tubules’ in confocal micrographs and EM tomograms of ischemic border zone tissues following myocardial infarction. In dSTORM tissue imaging, we have observed analogous macro-tubules in a small subset of ventricular myocytes in aged (70–110 week old) mice which display normal cardiac function (Figures 3E,F ).…”
Section: Utility Of Nanoscale Resolution For Studying Couplon Remodelmentioning
confidence: 98%